(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the spatio-temporal evolution of the vegetation cover in the Goiabal area, in the municipality of Calçoene/AP, observing the vegetation dynamics in relation to the influences of El Niño and La Niña climatic phenomena. The analyzes were performed at 5-year intervals, in the years 2010, 2015 and 2020, using orbital data from satellite images, based on active chlorophyll reflectance (NDVI - Normalized Difference Vegetation Index). The images used were from the LANDSAT 5 / TM sensor (Thematic Mapper) and LANDSAT 8 / OLI (Operation Land Imager) and TIRS (Thermal Infrared Sensor) sensors. The NDVI for the dense vegetation class ranged from 0.301 to 0.857, as the lowest value for the year 2015 where the occurrence of the phenomenon (El Niño) is classified as strong intensity, the sparse vegetation class has NDVI values ​​ranging from 0.155 to 0.804, exposed soil ranges from -0.050 to 0.301, with the highest value referring to the year 2015, which has the highest area growth among the classes. The year 2010 is classified as moderate (La Niña) and 2020 as weak intensity (El Niño), not causing major changes in the observed classes. The application of NDVI allowed identifying the vegetation dynamics present in the area and evaluating its changes over time. The Goiabal area has undergone changes in vegetation cover.